2014
DOI: 10.1155/2014/637858
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Antimicrobial Activity of Copper Oxide Nanoparticles

Abstract: We studied the structural and antimicrobial properties of copper oxide nanoparticles (CuO NPs) synthesized by a very simple precipitation technique. Copper (II) acetate was used as a precursor and sodium hydroxide as a reducing agent. X-ray diffraction patter (XRD) pattern showed the crystalline nature of CuO NPs. Field emission scanning electron microscope (FESEM) and field emission transmission electron microscope (FETEM) demonstrated the morphology of CuO NPs. The average diameter of CuO NPs calculated by T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
142
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 399 publications
(171 citation statements)
references
References 9 publications
9
142
0
10
Order By: Relevance
“…Peaks were found in a diffractogram at an angle of 18 ∘ which indicated that the synthesized iron oxide nanoparticles were crystalline phase and also result was well matched with the JCPDS card number 19-0629 [30]. Similar kinds of results have been found in green synthesis of manetite nanoparticle [31].…”
Section: X-ray Diffractionsupporting
confidence: 73%
See 1 more Smart Citation
“…Peaks were found in a diffractogram at an angle of 18 ∘ which indicated that the synthesized iron oxide nanoparticles were crystalline phase and also result was well matched with the JCPDS card number 19-0629 [30]. Similar kinds of results have been found in green synthesis of manetite nanoparticle [31].…”
Section: X-ray Diffractionsupporting
confidence: 73%
“…X-ray diffraction pattern was obtained from Seifert XRD 3003 diffractometer having the Cu-K radiation source which was used to confirm the presence of green synthesized nanoparticles. The samples were scanned in the 2 ranges of 10 to 70 ∘ C with the scan rate of 0.04 ∘ /sec and the average particle size was also to be calculated from the diffractogram using Debye-Scherrer's formula [18]. The structural morphology of prepared nanoparticles was carried out by JSM 6360 scanning electron microscope with an accelerating voltage between 10 and 20 KV under the vacuum condition.…”
Section: Characterization Of Nanoparticlesmentioning
confidence: 99%
“…Compared with ordinary copper oxide powder, the nano particles of copper oxide show superior catalytic activity and selectivity. It has excellent antimicrobial activity against various bacterial strains [2]. The CuO-NPs are using in removal of dyes [3], nanoparticulate film fabrications [4], gas sensors [5], semiconductors [6], organic catalysis [7], solar energy transformation [8], and many more.…”
Section: Introductionmentioning
confidence: 99%
“…Данный способ позволяет получать наночасти-цы металлов (или оксидов металлов) с низким распределением разме-ров и контролируемой морфологией. В качестве неорганических предшественников наночастиц меди используют ацетат меди Cu(CH 3 COO) 2 Важную роль в качестве восстанавливающего агента соли меди играет избыток аскорбиновой кислоты [21][22][23] (возможно использова-ние гидроксида натрия [16,24] или боргидрида натрия [10]), предот-вращающий окисление наночастиц меди [25][26][27]. Антиокислительные свойства аскорбиновой кислоты проявляются благодаря способности присоединять свободные радикалы с помощью электронного пожертво-вания по донорно-акцепторному механизму:…”
Section: химические методы подготовки медиunclassified
“…При использовании восстановителя гидроксида натрия качество меди получается одинаковым, независимо от применяемого неоргани-ческого предшественника [16,24]. Сходны как геометрические свой-ства, так и фазовое состояние меди.…”
Section: химические методы подготовки медиunclassified